Comparison of outcomes obtained from nominal group technique and survey method: An empirical investigation - Islam, Rafikul (Inderscience Enterprises Ltd, 2018)
Nominal group technique (NGT) is a method wherein brainstorming is used to generate ideas in large number on a certain issue. Afterwards, the ideas are prioritized by using a suitable voting scheme. The result of a nominal group (NG) session is basically a hierarchical list of ideas. The number of participants of a NG session normally ranges from six to ten people. Together they make the hierarchical list of ideas through voting. The objective of the present research is to examine the difference, if any, between the results obtained from a NG session and a succeeding follow-up survey. The results from two experiments suggest a close association between the ranks of ideas obtained from NGT and survey method. The findings of the present research emphasise the effectiveness of NGT in terms of idea generation and reliability of ranking of ideas.